National Public Health Burden Estimates of Endocarditis and Skin and Soft-Tissue Infections Related to Injection Drug Use: A Review. (2nd September 2020) - See, Isaac; Gokhale, Runa H; Geller, Andrew; Lovegrove, Maribeth; Schranz, Asher; Fleischauer, Aaron; McCarthy, Natalie; Baggs, James; Fiore, Anthony
Abstract: Background: Despite concerns about the burden of the bacterial and fungal infection syndromes related to injection drug use (IDU), robust estimates of the public health burden of these conditions are lacking. The current article reviews and compares data sources and national burden estimates for infective endocarditis (IE) and skin and soft-tissue infections related to IDU in the United States. Methods: A literature review was conducted for estimates of skin and soft-tissue infection and endocarditis disease burden with related IDU or substance use disorder terms since 2011. A range of the burden is presented, based on different methods of obtaining national projections from available data sources or published data. Results: Estimates using available data suggest the number of hospital admissions for IE related to IDU ranged from 2900 admissions in 2013 to more than 20 000 in 2017. The only source of data available to estimate the annual number of hospitalizations and emergency department visits for skin and soft-tissue infections related to IDU yielded a crude estimate of 98 000 such visits. Including people who are not hospitalized, a crude calculation suggests that 155 000–540 000 skin infections related to IDU occur annually. Discussion: These estimates carry significant limitations. However, regardless of the source or method, the burden of disease appears substantial, with estimates of thousands of episodes of IE among persons with IDU and at least 100 000 persons who inject drugs (PWID) with skin and soft-tissue infections annually in the United States. Given the importance of these types of infections, more robust and reliable estimates are needed to better quantitate the occurrence and understand the impact of interventions.